IMPLEMENTATION OF DIGITAL LITERACY UNDER CONDITIONS OF THE FUTURE CHANGES IN ACCOUNTANT PROFESSION (Economic journal of Lesya Ukrainka Volyn National University, 2020)
Introduction. The article examines the current trends in the accountant profession. The conservative context of the accountant profession is changed by the non-standard thinking of a specialist, who being a manager-administrator and analyst makes decisions justified by legal requirements, minimizes risks of operating activity as well as demonstrates leadership and communication skills, ability to quickly evaluate the situation. It has gained key importance in business.The purpose of the article is to study the introduction of digital literacy, digital culture in the conditions of the modern accountant professional competencies formation and future changes of this profession.Results. Digital transformations in the economy affect the accountant profession including both the formation of his professional competencies and digital literacy. In the context of digital transformations in the economy, the diverse world of IT solutions offers the accountant many tools from which he must choose the combination that reflects the task on organization of accounting at the enterprise.The modern accountant adopts a variety of programs for accounting and tax registration, freely guides in their advantages and selects the best decision for the enterprise. It designs business processes and sets the task for the developers in accordance with the enterprise accounting policies. He manages the new technology.In practice, the important role of keeping the accountant's professional priorities is that he deals with the limited staff and has to:‒ independently select software and hardware for automation of accounting system;‒ set up accounting software;‒ independently search for ways to master the latest software products.And this requires having the appropriate level of competences acquired in the educational institutions training and the development and improvement of organizational nature competencies needed in the conditions of a particular business entity.Conclusions. Thus, in the future a professional accountant is viewed as a driver of changes in skills that potentially affect competences and personal qualities. In doing so, the professional digital accountants will be asked for decades to come in order to help the educators, employers, and professional organizations to articulate the transformation of the accountant profession.
Keywords: digital literacy, accountant profession, professional competences, automation, software, management